(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The state discusses the etiology of fibrocystic disease (FCB) or mastopathy, benign breast dysplasia (DDMJ), fibroadenoma (FA) and breast cancer (RMJ), precancerous condition, as well as the relationship of risk factors with increased breast risk, more serious causes, pathogenesis and morphogenesis, the mechanism of development of apoptosis factors In the breast cell. FCB and breast cancer have a common etiology, most of the risk factors are the same. Numerous risk factors disrupt the hormonal balance in a woman’s body, cause hyperestrogenism and hyperproliferation of the epithelium in breast tissues, which leads to the development of PCB, in the presence of congenital or acquired gene damage – to the development of breast cancer. The morphological examination of breast tissue obtained during biopsy is crucial in assessing the risk of breast cancer in a patient with FCB. The risk of breast cancer does not increase or is minimal in the non- proliferative form of FCB. With the proliferative form of the FKB gland, the atypical risk of RMJ increases by 2 times, with atypical – by 4 times. The risk of developing breast cancer in FCB with ductal or lobular carcinoma in place is maximum and can increase by 12 times.